A collaboratively produced model of service design for children and young people with common mental health problems - Steven Pryjmachuk; Susan Kirk; Claire Fraser; Nicola Evans; Rhiannon Lane; Jodie Crooks; Rose McGowan; Georgia Naughton; Liz Neill; Elizabeth Camacho; Peter Bower; Penny Bee; et al. (BMC, 2024)
Abstract Background Little is known about the effectiveness of, and implementation complexities associated with, service delivery models for children and young people (CYP) experiencing 'common' mental health problems such as anxiety, depression, behavioural difficulties and self-harm. This paper outlines how a model for high-quality service design for this population group was developed by identifying available services, their effectiveness, cost-effectiveness and acceptability, and the barriers and enablers to access. Methods Sequential, mixed-methods design, combining evidence syntheses (scoping and integrative reviews of the international literature) with primary research (a collective case study in England and Wales). Data from these two elements were collaboratively synthesised in a subsequent model-building phase. Results The scoping review yielded a service model typology. The integrative review found effectiveness evidence only for four models: collaborative care (the only service model to also have cost-effectiveness evidence), outreach approaches, brief intervention services and an organisational framework called 'Availability, Responsiveness and Continuity'. No service model seemed more acceptable than others. Three case study themes were identified: pathways to support; service engagement; and learning and understanding. The model-building phase identified rapid access, learning self-care skills, individualised support, clear information, compassionate and competent staff and aftercare planning as core characteristics of high-quality services. These characteristics were underpinned by four organisational qualities: values that respect confidentiality; engagement and involvement; collaborative relationships; and a learning culture. Conclusions A consistent organisational evidence-base for service design and delivery in CYP's mental health spanning many years appears to have had little impact on service provision in England and Wales. Rather than impose - often inflexible and untested - specific local or national models or frameworks, those commissioning, designing and delivering mental health services for CYP should (re)focus on already known, fundamental components necessary for high-quality services. These fundamental components have been integrated into a collaboratively produced general model of service design for CYP with common mental health problems. While this general model is primarily focused on British service provision, it is broad enough to have utility for international audiences.